Perceived influence of parenting styles on the body esteem of male students at the University of the Witwatersrand. - Dubazana, Zanele (My University, 2010)
This study set out to examine the perceived influence of parenting styles on the body esteem of male students at the University of the Witwatersrand. Ninety eight first year male students in the age range of 18-22 years, from the medical faculty at the University of the Witwatersrand enrolled in psychology participated in the study. Four scales were administered: a demographic questionnaire, the Body Esteem Scale, the Parental Authority Questionnaire, and Rosenberg’s Self-Esteem Scale. The results indicate that there is no significant correlation between perceived paternal and maternal parenting styles and the body esteem and self-esteem, respectively of the male students. There are no self-esteem and body esteem differences according to race. The tripartite theory suggests that a combination of peers, parents and media have some level of influence on body esteem and self esteem perceptions (Shroff & Thompson, 2005). The theory suggests that tripartite influential factors play a different role at different times of an individual’s life (Thompson, Coovert & Storner, 1999). Parents play a crucial role at the pre-adolescent stage; peers are more influential at the adolescent stage and the media is more influential at the early adulthood stage (Levine & Harrison, 2004). Vygotsky’s socio cultural theory indicates that the child’s learning development is affected by the culture in which he or she is raised (Vygotsky, 1981). According to Vygotsky’s perspective, the community at large, specifically adults and peers, are lifelong role players that serve as guides to support cognitive growth (Vygotsky, 1986). These theories bring the variables discussed in this study into theoretical perspective and bring out the relevance of socialisation and identity formation (Vygotsky, 1981). The study concludes that there are many factors that can influence males at different stages of their lives; parents do not appear to be the leading influential factor at the stage in this study.